2015
DOI: 10.1111/rda.12539
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Development of Embryonic Age by Organogenesis in Domestic Dogs and Cats

Abstract: The precise determination of the embryonic chronology is very important in reproductive biotechnologies, especially in estimating embryonic age. Thus, there is a need for greater knowledge and standardization for determining the chronology of embryonic development and functional morphology. We describe aspects of embryonic development in two domestic carnivores to add knowledge about organ peculiarities and for application in veterinary practice, in prenatal development and in the biotechnology fields. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…Embryos with 1.2-1.5 cm (AE26/30 days) had pigmented optic placode as observed in equine (1.5 cm) and bovine (1.4 cm) (Assis-Neto et al 2009;Franciolli et al 2011); cranial neuropore opened showing the fourth ventricle and nasal cavity, midbrain, cervical curvature and tail; the pharyngeal arches were distinct and limbs were developed; Pieri et al (2015) showed in dog and cats (1.7 cm) similar results in limbs, and Roballo et al (2013) described the pharyngeal arches development at the same days. Large vessels ventrally to the midgut was visible, these vessels connect the yolk sac with the primitive gut; in human embryos, this phenomenon happens at the beginning of the fourth week (Moore and Persaud 2008).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Embryos with 1.2-1.5 cm (AE26/30 days) had pigmented optic placode as observed in equine (1.5 cm) and bovine (1.4 cm) (Assis-Neto et al 2009;Franciolli et al 2011); cranial neuropore opened showing the fourth ventricle and nasal cavity, midbrain, cervical curvature and tail; the pharyngeal arches were distinct and limbs were developed; Pieri et al (2015) showed in dog and cats (1.7 cm) similar results in limbs, and Roballo et al (2013) described the pharyngeal arches development at the same days. Large vessels ventrally to the midgut was visible, these vessels connect the yolk sac with the primitive gut; in human embryos, this phenomenon happens at the beginning of the fourth week (Moore and Persaud 2008).…”
Section: Discussionmentioning
confidence: 81%
“…); cranial neuropore opened showing the fourth ventricle and nasal cavity, midbrain, cervical curvature and tail; the pharyngeal arches were distinct and limbs were developed; Pieri et al. () showed in dog and cats (1.7 cm) similar results in limbs, and Roballo et al. () described the pharyngeal arches development at the same days.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations